Production of carotenoids by yeast Rhodotorula glutinis CCT-2186 and their extraction using alternative solvents - Mussagy, Cassamo Ussemane [UNESP] (2021)
This thesis consists of the investigation and optimization of sustainable strategies to enhance carotenoids production from yeast Rhodotorula glutinis CCT- 2186 (R. glutinis) and their extraction by means of ionic liquids (ILs) and bio-based solvents. The interest on carotenoids such as β-carotene, torulene and torularhodin relies on the plethora of relevant properties of these products and their commercial value for food, feed, cosmetic and pharmaceutical industries. However, to make carotenoids more accessible in a sustainable way, their production from microbial sources is of paramount importance. Concerning the production of carotenoids from R. glutinis yeast there are still processual challenges, such as the improvement of production yields and development of efficient and sustainable extraction platforms. Initially, different statistical experimental designs were applied to improve carotenoids production and the best bioprocess was scaled-up to a 5 L stirred-tank bioreactor. Since the carotenoids are produced intracellularly, requiring appropriate cell-disrupting and extraction methodologies for their recovery, subsequently, the development of more benign and effective extraction/purification platforms was evaluated. A comprehensive study using aqueous solutions of ionic liquids (ILs) for solid-liquid extraction (SLE) processes was carried out, following the carotenoids purification using a three-phase partitioning system composed of aqueous solutions of ILs and inorganic salts. To gather additional information on the phase separation mechanisms, aqueous biphasic systems (ABS) composed of ILs and inorganic salts were determined and characterized. Afterward, the potential of bio-based solvents was evaluated, with the purpose of designing a more efficient and ecofriendly extraction process for recovery of the intracellular carotenoids from R. glutinis. In this study it was designed and optimized an integrated downstream platform using a ternary mixture of bio-based solvents (ethyl acetate/ethanol/water) with isolation and polishing of carotenoids as well as the recycling of the solvents. The overall sustainability of the proposed technology was assessed in terms of solvents recyclability and carotenoids polishing, and the environmental impact of the platform through a life cycle assessment (carbon footprint). This thesis demonstrates the importance of combined organic and inorganic nitrogen sources to supplement the nutritional media for cultivation of R. glutinis and production of carotenoids, and that ILs and mixed bio-based solvents can be used to design simple, efficient and sustainable platforms for the recovery of intracellular carotenoids from microbial biomass.